The management of patients with functional stroke: speech and language therapists' views and experiences. Issue 14 (3rd July 2022) - Barnett, Caroline; Mitchell, Claire; Tyson, Sarah
Abstract: Purpose: Patients with functional stroke can present with functional speech, language or swallowing symptoms, which are managed by speech and language therapists (SLTs). The aim of this study was to explore SLTs' views and experiences of working with patients with functional stroke. Methods: Constructivist grounded theory approach was used. Semi-structured interviews were the method of data collection. Constant comparative analysis was used to analyse data. Participants were eligible if they were SLTs who thought they had experience of working with functional stroke. Results: 12 participants were interviewed. Patients with functional stroke were a common occurrence on participants' caseloads; yet they felt patients do not receive optimum care. All participants wanted to help their patients, yet felt they were working within a multitude of barriers to effective input. These included: stigma about the diagnosis, lack of pre-qualification training, quick discharge from inpatient settings, lack of access to mental health services and lack of clinical guidelines and care pathways. Conclusions: As healthcare professionals, participants were keen to help their patients. However, they felt they did not have the skills or knowledge to help which caused professional turmoil. Reducing stigma and increasing awareness and knowledge of functional stroke are required to improve patient outcomes.